USE OF SEWAGE SLUDGE ON EUCALYPTUS SALIGNA INITIAL GROWTH - Zabotto, Alessandro Reinaldo; Feitosa, Maria Fernanda; Gomes, Leticia Danielle Longuini; Tavares, Armando Reis; Boas, Roberto Lyra Villas (ENERGIA NA AGRICULTURA, 2021)
USE OF SEWAGE SLUDGE ON EUCALYPTUS SALIGNA INITIAL GROWTH ALESSANDRO REINALDO ZABOTTO1, MARIA FERNANDA FEITOSA2, LETICIA DANIELLE LONGUINI GOMES2, ARMANDO REIS TAVARES3, ROBERTO LYRA VILLAS BOAS1 1 Department of Forestry, Soil and Environment Science, Paulista State University (UNESP), Avenida Universitária, nº 3780, 18610-034, Botucatu-SP, Brasil. 2 Instituto de Pesquisas Ambientais, Av. Miguel Stéfano, 3687, 04301-902, São Paulo-SP, Brasil. 3 Department of Fruit Culture, Agronomic Institute (IAC), Av. Luís Pereira dos Santos, 1500, 13214-820, Jundiaí-SP, Brasil. ABSTRACT: This study aimed to evaluate the effect of different doses of sewage sludge on Eucalyptus saligna initial growth. E. saligna seedlings were cultivated for 120 days in pots containing soil (control), soil + 30 Mg ha-1 sewage sludge, soil + 60 Mg ha-1 sewage sludge and soil + 90 Mg ha-1 sewage sludge. The chemical analyses of soils and macro- and micronutrient contents in leaves and biometric, biomass and physiological variables were evaluated. The treatments with sewage sludge were statistically higher than the control treatment for all variables. Treatments of 30 and 60 Mg ha-1 sewage sludge were higher than 90 Mg ha-1 sewage sludge for plant growth. The liquid photosynthesis (A), stomatal conductance (Gs) and transpiration (E) of Eucalyptus saligna in all treatments were higher than the Control treatment. We recommend the application of 30 Mg ha-1 sewage sludge for the initial growth of Eucalyptus saligna seedlings. Moreover, the use of sewage sludge as substrate conditioner and fertilizer for Eucalyptus saligna seedling cultivation is an adequate and sustainable way to manage this urban waste. Keywords: biosolid, fertilization, seedlings, plant growth. UTILIZAÇÃO DE LODO DE ESGOTO NO CRESCIMENTO INICIAL DE EUCALYPTUS SALIGNA RESUMO: O estudo teve como objetivo avaliar o efeito de diferentes doses de lodo de esgoto no crescimento inicial de Eucalyptus saligna. Mudas de E. saligna foram cultivadas por 120 dias em vasos contendo solo (controle), solo + 30 Mg ha-1 lodo de esgoto, solo + 60 Mg ha-1 lodo de esgoto e solo + 90 Mg ha-1 lodo de esgoto. Foram avaliadas as análises químicas dos solos e teores de macro e micronutrientes nas folhas e variáveis ​​biométricas, biomassa e fisiológicas. Os tratamentos com lodo de esgoto foram estatisticamente superiores ao tratamento controle para todas as variáveis. Os tratamentos de 30 e 60 Mg ha-1 de lodo de esgoto foram superiores a 90 Mg ha-1 de lodo de esgoto para o crescimento das plantas. A fotossíntese líquida (A), condutância estomática (Gs) e transpiração (E) de Eucalyptus saligna em todos os tratamentos foram superiores ao tratamento Controle. Recomendamos a aplicação de 30 Mg ha-1 de lodo de esgoto para o crescimento inicial de mudas de Eucalyptus saligna. O uso do lodo de esgoto como condicionador de substrato e fertilizante para o cultivo de mudas de Eucalyptus saligna é uma forma adequada e sustentável de gerenciar esse resíduo urbano. Palavras-chave: biossólido, fertilização, mudas, crescimento de plantas.